ANALISIS STRATEGI KOMUNIKASI DINAS KESEHATAN KOTA BANJARMASIN DALAM MENSOSIALISASIKAN PROGRAM PENCEGAHAN PENYAKIT DEMAM BERDARAH‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬ - Abid Rahmatullah; Muji Rahman; Norlaily Yasmin; Bahdiah; Marhaeni Fajar Kurniawati (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease that contributes to the number of deaths with hundreds of deaths each year, especially in densely populated urban areas such as Brazil, South America, the Caribbean, Southeast Asia, and India. This study aims to analyze the communication strategy of the Banjarmasin City Health Office in socializing the DHF prevention program. The research method uses a qualitative phenomenological approach. Informants namely one head of the health service and four health service officers. Data analysis, namely bracketing, intuitive, analyzing, and describing. Primary data obtained from semi-structured interviews. Secondary data was obtained from official documents and reputable journals for the last five years. The results showed that the Health Office of the City of Banjarmasin had not been successful in persuading the residents to try to prevent DHF, with the number of victims continuing to increase each year. Health service workers experience anxiety that has the potential to arise due to the change of seasons during the rainy season, the dynamics of government regulations against DHF, the increased workload, especially during the Covid-19 pandemic, and the location of the place of work. Program enrichment in the form of debriefing training in dealing with DHF for health service officers in cases of vulnerable places needs to be emphasized in helping psychological and mental readiness so that it can reduce the level of anxiety when there is a change in weather followed by an increase in the number of DHF incidents.